Anomalies in the internal friction and sound velocity in the high-temperature superconductor La1.8Sr0.2CuO4 - Esquinazi, P.; Luzuriaga, J.; Durán, C.; Esparza, D.A.; D'Ovidio, C. (American Physical Society, 1987)
Fil: Esquinazi, P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina